2017
DOI: 10.1136/postgradmedj-2017-134968
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for amendment in type, duration and setting of prescribed outpatient parenteral antimicrobial therapy (OPAT) for adult patients with cellulitis: a retrospective cohort study and CART analysis

Abstract: Increased age, NPSS and immunocompromise were associated with OPAT amendment. These identified risk factors can be used to support an evidence-based approach to patient selection for OPAT in cellulitis. The CART algorithm has good specificity but lacks sensitivity and is shown to be inferior in this study to logistic regression modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…CART decision tree analysis has been used to assist clinical decision making across a wide assortment of health conditions, their diagnosis or treatment, and outcome predictions. 7,8,9,10,11,1213 In rapid response to a pandemic novel coronavirus, the local testing center established testing criteria on knowledge of inpatient symptoms, including fever, cough and shortness of breath. 14 We found that among those referred for outpatient testing, the symptoms that were significantly more frequent among cases than among non-cases differed from those typically reported among inpatients with COVID-19 infection and on which early identification of possible cases were based.…”
Section: Discussionmentioning
confidence: 99%
“…CART decision tree analysis has been used to assist clinical decision making across a wide assortment of health conditions, their diagnosis or treatment, and outcome predictions. 7,8,9,10,11,1213 In rapid response to a pandemic novel coronavirus, the local testing center established testing criteria on knowledge of inpatient symptoms, including fever, cough and shortness of breath. 14 We found that among those referred for outpatient testing, the symptoms that were significantly more frequent among cases than among non-cases differed from those typically reported among inpatients with COVID-19 infection and on which early identification of possible cases were based.…”
Section: Discussionmentioning
confidence: 99%